2009
DOI: 10.1371/journal.pone.0005032
|View full text |Cite
|
Sign up to set email alerts
|

Nobody Is Perfect: ERP Effects Prior to Performance Errors in Musicians Indicate Fast Monitoring Processes

Abstract: BackgroundOne central question in the context of motor control and action monitoring is at what point in time errors can be detected. Previous electrophysiological studies investigating this issue focused on brain potentials elicited after erroneous responses, mainly in simple speeded response tasks. In the present study, we investigated brain potentials before the commission of errors in a natural and complex situation.Methodology/Principal FindingsExpert pianists bimanually played scales and patterns while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 57 publications
8
91
2
6
Order By: Relevance
“…Results showed no negativity after performance errors (compared to correct notes) in the time window of the feedback ERN/N200, elicited by the feedback manipulations. Performance errors only elicited an increased negativity prior to feedback onset and an increased positive potential around 280 msec after feedback onset (for further details on the ERPs of self-generated errors, see Maidhof et al, 2009). perception condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed no negativity after performance errors (compared to correct notes) in the time window of the feedback ERN/N200, elicited by the feedback manipulations. Performance errors only elicited an increased negativity prior to feedback onset and an increased positive potential around 280 msec after feedback onset (for further details on the ERPs of self-generated errors, see Maidhof et al, 2009). perception condition.…”
Section: Discussionmentioning
confidence: 99%
“…ANOVAs were conducted with factor tone (correctly played, incorrectly played) for time windows of −150 to −80 msec, 140 to 240 msec, and 270 to 330 msec over a frontocentral ROI. For further details on the ERPs of self-generated errors, see Maidhof, Prinz, Rieger, & Koelsch (2009).…”
mentioning
confidence: 99%
“…During copy typing, the template is an additional source of information. For error detection another source of information may be predictive processes, which predict movement consequences based on current motor commands (Rabbitt, 1978; Wolpert and Flanagan, 2001; Maidhof et al, 2009; see below). In the following we discuss each of these sources of information and how attention to them might be influenced by typing style.…”
Section: Introductionmentioning
confidence: 99%
“…However, the comparison of intended movement consequences and internally predicted movement consequences can lead to the detection of (some) errors in the absence of feedback. Errors may be detected even before the action is fully executed (i.e., before the actual movement consequence is available), even though they may still be committed (Maidhof et al, 2009). Subjectively, internally prediction may result in the impression that something is about to go wrong in the absence of any other feedback.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of piano performance, two recent electrophysiological studies found that around 70 ms prior to performance errors a negative component -termed pre-ERN and resembling the post-response ERNwas elicited in the event-related potentials (ERP; Herrojo Ruiz et al, 2009a;Maidhof et al, 2009). Performance errors (hereafter termed errors) in these settings consisted of playing an incorrect key (note) on the piano.…”
Section: Introductionmentioning
confidence: 99%